Use of vermicompost as a substrate for the production of Eucalyptus grandis and Corymbia citriodora seedlings - Steffen, Gerusa Pauli Kist (2011)
The aim of this work was to evaluate the vermicompost efficiency in the seedlings of two eucalyptus species production. The experiment was developed in greenhouse conditions, substrate constituted by different vermicompost proportions and peat for the E. grandis and C. citriodora seedling production. The experimental design was entirely casualized with seven treatments and eight repetitions. After 100 days of experiment were evaluated: seedling height, fresh and dry biomass of aerial part, root volume, dry biomass of the root and Dickson quality index (DQI). The treatment constituted by 80% vermicompost and 20% peat presented the highest results in height, root volume and dry mass of the aerial part and roots. For the species C. citriodora was observed that the vermicompost addition to the peat in the proportions from 40% to 80% was shown efficient in the seedlings growth. The treatment constituted by 80% vermicompost and 20% peat provided highest height and dry mass of the aerial part seedlings and the treatment constituted by 60% vermicompost and 40% peat provided highest root volume. The proportions 60% and 80% vermicompost added to the peat increase the E. grandis and C. citriodora seedlings production.